Reconstructing Fluctuations of La Mare Glacier (Eastern Italian Alps) in the Late Holocene: New Evidence for a Little Ice Age Maximum Around 1600 AD. Issue 3 (21st April 2014) - Carturan, Luca; Baroni, Carlo; Carton, Alberto; Cazorzi, Federico; Fontana, Giancarlo Dalla; Delpero, Claudio; Salvatore, Maria Cristina; Seppi, Roberto; Zanoner, Thomas
Abstract Field observations, old terrestrial photographs and maps, aerial orthophotos and detailed geomorphological mapping were used for compiling and validating a 119‐year cumulative record of terminus changes for La Mare Glacier, Eastern Italian Alps. Late Holocene glacier maxima preceding direct observations were reconstructed by applying age dating techniques (radiocarbon and lichenometry) to glacial deposits in the proglacial area of the glacier. Results show that the glacier reached its maximal position around 1600 ad, followed by smaller advances in the eighteenth century, while in the nineteenth century it did not reach or overrun these positions. A similar behaviour for neighbouring glaciers was reported by previous works, documenting absolute Late Holocene maxima in the seventeenth or eighteenth centuries. By contrast, multi‐century reconstructions available for the north‐western Alps show that in the nineteenth century, glaciers were at their maximum or very close to previous maxima achieved in the first half of the seventeenth century. Climatic causes for these discrepancies have been examined, analyzing multi‐proxy climatic reconstructions starting in 1500 ad, but also morphodynamic processes linked to the bedrock characteristics of La Mare Glacier could have played a role in modulating its response to climatic changes.